Hubungan Dukungan Keluarga Dengan Kepatuhan Melakukan Kontrol Rutin Pada Penderita Diabetes Mellitus Di Puskesmas Kalibagor Banyumas - Prawesty Desy Nugraheni; Ita Apriliyani; Noor Yunida Triana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diabetes Mellitus is a disease characterized by blood glucose levels above 90-120 mg/dl. A person suffering from Diabetes Mellitus must carry out routine control for the rest of his life to control blood sugar and prevent complications. Family support is important during the treatment period. One form of support is giving motivation to comply with routine controls. The aim of the study was to determine the relationship between family support and adherence to routine control of DM sufferers at the Kalibagor Health Center. The research method is descriptive correlation (cross sectional) and uses a non-probability sampling technique (total sampling) with 45 respondents participating in prolanis activities. This study used a questionnaire in the form of family support. Using the Spearman rank test, the results of the study included good family support of 88.9% and adherence to routine control of 88.9%. Spearman rank test results with a p-value = 0.000 (p <0.05) with a moderate level of closeness (R = 0.550), which means that there is a significant relationship between family support and compliance with routine control of diabetes mellitus patients at the Kalibagor Health Center. So, it is suggested that respondents adhere to routine control with the help of family support to avoid complications caused by diabetes mellitus. The better the family support, the more obedient the patient is to carry out routine controls.